1993
DOI: 10.1161/01.res.72.1.167
|View full text |Cite
|
Sign up to set email alerts
|

Altered left atrial compliance after atrial appendectomy. Influence on left atrial and ventricular filling.

Abstract: Previous studies have shown regional differences in atrial distensibility. We studied 12 open-chest dogs to test the hypothesis that left atrial compliance is decreased after removal of the left atrial appendage and to determine the effect of altered atrial compliance on atrial reservoir and conduit function. Sonomicrometer crystal pairs were used to measure the long- and short-axis diameters of the left atrium over a wide range of intracardiac pressures and volumes obtained by intravenous hetastarch infusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
1
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(97 citation statements)
references
References 23 publications
5
89
1
2
Order By: Relevance
“…The positive impact of enhanced atrial compliance and maintained reservoir to conduit properties on global cardiac performance has previously been reported for the LA (4,11,12,14). In an elegant computer model, Suga (27) also suggested that increased atrial distensibility would improve cardiac performance and concluded that a "flexible atrium" (increased receptacle capabilities) could substantially impact the heart's output.…”
Section: Discussionmentioning
confidence: 68%
“…The positive impact of enhanced atrial compliance and maintained reservoir to conduit properties on global cardiac performance has previously been reported for the LA (4,11,12,14). In an elegant computer model, Suga (27) also suggested that increased atrial distensibility would improve cardiac performance and concluded that a "flexible atrium" (increased receptacle capabilities) could substantially impact the heart's output.…”
Section: Discussionmentioning
confidence: 68%
“…Reservoir and conduit functions of the right atrium were calculated by integrating RA inflow (combined SVC and IVC flow) during RV systole (reservoir) and RV diastole (conduit) (16,17,30). Because the tricuspid valve is closed during RV systole, all blood that enters from the cavae during this period is reserved in the atrium (coronary sinus return was temporarily interrupted during data collection).…”
Section: Methodsmentioning
confidence: 99%
“…The significance of the LAA in fluid balance has been reinforced in humans after clamping of the LAA during cardiac surgery yielded increased LA and left ventricular filling pressures [8]. Animal studies have also shown that by removing the LAA, reduction of both LA compliance and LA function occurs [11]. Notably, a dramatic reduction in cardiac output, of nearly 50%, was witnessed in guinea pigs following ligation of the LAA.…”
Section: Laa Physiologymentioning
confidence: 99%